Modelling Height-Age Curves in Fast-Growing Deciduous Tree Species from Terai Region of Kumaun Foothills - Tripathi, Mayank (Journal of Forest and Natural Resource Management, 2024)
Modelling tree and stand growth is one of the most significant aspects of forest science and simulation modelling. Such analysis helps in understanding forest dynamics in terms of growth and yield, survival and mortality patterns, biomass partitioning and carbon sequestration capacity of forest stands. In this study, a 3- parametric Chapman- Richards function was applied to evaluate cumulative, absolute and relative height growth curves in three fast growing tree species from Fabaceae family viz. Dalbergia sissoo, Delonix regia and Acacia catechu. Relative growth rates (RGRs) were calculated both as a function of “age” and “size” i.e., time and size dependent RGR. Cumulative, absolute and relative growth rate functions fitted quite well to all three species. Upper asymptotic values for total tree height were found to be maximum in D. sissoo (5.61 m), followed by A. catechu (4.97 m) and D. regia (3.34 m). Size- standardized RGR analysis showed that due to low rate of decline, D. sissoo had a superior RGR throughout most of its height development, despite its initial RGR being much less than those of other two species. Residual analysis of the cumulative datasets displayed absence of outliers, and the data were found to be normally distributed. Model parameters for all three species were statistically significant (P<0.005). The study thus investigates function- derived growth rates in plant growth modelling.